Evaluation and analysis of a secure voting-based aggregated signatures authentication and revocation protocol for 5 G-V2X communication - Shimaa A. Abdel Hakeem; HyungWon Kim (Alexandria Engineering Journal, 2023)
Security concerns in 5 G-V2X communication, including message authenticity, entity identification, and efficient malicious entity detection, necessitate innovative solutions. This paper introduces a novel protocol aimed at addressing security challenges in 5 G-V2X communication, focusing on authentication and misbehaving entity revocation. The protocol employs short bilinear pairing digital signatures for message authentication and pseudo-identity for entity verification. Key generation utilizes a Secret Splitting-based approach, distributing partial keys to vehicles within the same group, ensuring secure future communication. In terms of performance, our protocol excels in communication efficiency, costing only 280 bytes per message, the lowest among evaluated protocols. It also demonstrates competitive computation efficiency, with a signing time of 0.614 ms per message and a verification time of 5.035 ms per signature. Our innovative revocation method ensures timely detection and reporting of misbehaving entities, with an average detection time of 2.3 s and an average revocation time of 1.8 s. Our protocol enhances security in 5 G-V2X communication while maintaining superior communication and computation efficiency.